The Role of Work-Life Balance and Job Satisfaction as Predictors of Organizational Commitment - Nancy Yusnita; Hari Gursida; Erna Herlina (Jurnal Economia, 2022)
AbstractMuch of the research on organizational commitment has generated findings that organizational commitment considers to predict individual performance. The purpose of the study is to examine the factors that affect organizational commitment, namely work-life balance and job satisfaction. The study was conducted at PT. PLN Indonesia, and mainly utilized quantitative data (from questionnaires). The sample for the study consisted of 210 permanent employees of PT. PLN. Path analysis was used to find out the relationship among variables. The results showed, there was a positive effect of job satisfaction on organizational commitment; a negative effect work-life balance on organizational commitment; a positive effect of work-life balance on job satisfaction; a positive effect of work-life balance on organizational commitment through job satisfaction. This study proposed some recommendations tostrong indicators that have a high contribution to the organizational commitment in order to improve employees' organizational commitment. Keywords: organizational commitment, job satisfaction, work-life balance, individual performancePeran Kesimbangan Pekerjaan – Kehidupan Pribadi dan Kepuasan Kerja sebagai Prediktor Komitmen terhadap Organisasi pada Perusahaan Publik AbstrakBanyak penelitian berkaitan dengan komitmen organisasi menunjukkan bahwa komitmen organisasi diyakini memprediksi kinerja individu. Tujuan dari penelitian ini adalah untuk mengkaji faktor-faktor yang mempengaruhi komitmen organisasi yaitu work-life balance dan kepuasan kerja. Penelitian dilakukan di PT. PLN Indonesia, dan menggunakan data kuantitatif (dari kuesioner). Sampel penelitian terdiri dari 210 karyawan tetap PT. PLN. Analisis jalur digunakan untuk mengetahui hubungan antar variabel. Hasil penelitian menunjukkan, terdapat pengaruh positif kepuasan kerja terhadap komitmen organisasi; pengaruh negatif work-life balance terhadap komitmen organisasi; pengaruh positif work-life balance terhadap kepuasan kerja; pengaruh positif work-life balance terhadap komitmen organisasi melalui kepuasan kerja. Penelitian ini mengusulkan beberapa rekomendasi indikator kuat yang memiliki kontribusi tinggi terhadap komitmen organisasi dalam rangka meningkatkan komitmen organisasi karyawan.            Kata kunci: komitmen terhadap organisasi, kepuasan kerja, keseimbangan Pekerjaan-Kehidupan Pribadi, kinerja individu